INFLUENCE COVID-19 ON RECEIVING DONATIONS AND MANAGEMENT IN NON-PROFIT INSTITUTIONS - Yuliana Sri Purbiyati; Maria Widyastuti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Non-profit institutions, even if they are religious institutions, cannot be separated from finances, how they earn and how they are managed. This research is a qualitative research with a case study approach. Data obtained through observation, interviews, and documentation. This research tries to dissect how the Catholic Church in West Surabaya Diocese of Surabaya Diocese struggles to manage finances during the co-19 pandemic. There are two issues in this research, namely whether the Covid-19 pandemic has had an impact on the collection income of the Catholic Church and on the impact that has arisen on the income of church collections during the Covid-19 pandemic, and how the Catholic Church has financed its activities. The results of the study revealed that only at the beginning of the pandemic, some churches experienced ups and downs in their collection income, but after getting used to it; the collection income became stable again. In financing its activities, namely routine activities, programs, worship, and charities, all the Church manages from the finances of the congregation's collections and donations. During this pandemic, the Catholic Church of the West Surabaya Diocese of the Surabaya Diocese did not raise funds. The pure church only accepts congregational collections and donations from its own congregation. Keywords: non-profit organizations, catholic church, collections, donations, activities.